(3QSGdI aj GdChRGf GdTYQjIs - (3CMeO Hf YHO Gddg Hf SdjeGf GdJfhNj , CHh GdYdGA GdeYQj , J (B449 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdeYQi ESJYed CHh GdWjH QMeI Gddg ai GdChRGf GdJi PcQgG GdNdjd Hf CMeO CMO YTQ hRfkG GdWhjd hGdHSjW hGdhGaQ s
(3BNQgG (B:s
(3hGdcGa GdKGfjI ONjd hMQcJgG GTHGY hGdHGA Qhi hMQcJgG eLQi hGdgGA hUd GfJgi cdGe CHj GdYdGA Hf SdjeGf GdeYQi QMeg Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdSGOS hGdYTQhfs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B290s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9237) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs